Pengaruh Experiential Marketing terhadap Brand Loyalty yang Dimoderasi oleh Customer Satisfaction - Riani Oktavia; Hendrati Dwi; Dwi Nugraha, Yudha (Bandung Conference Series: Business and Management, 2024)
Abstract. This research has three objectives in terms of experiential marketing, brand loyalty, and customer satisfaction which focuses on Scarlett products sold on the Shopee application. These three goals include; (1) Knowing the general description of the variables used; (2) Investigating the positive and significant influence of experiential marketing on brand loyalty for Scarlett products; and (3) Investigating the moderating influence of customer satisfaction on the relationship between experiential marketing and brand loyalty for the Scarlett brand. The method used in this research was to carry out verification analysis on the results of the questionnaire distributed to 158 respondents and then readjusted, so that the respondents used were 120 respondents. The results of this research show that experiential marketing has a positive and significant influence on brand loyalty, and customer satisfaction can moderate the value of experiential marketing on brand loyalty. So, brand loyalty will increase along with the increase in experiential marketing. Apart from that, the increase in brand loyalty by experiential marketing can also be moderated by the increase in customer satisfaction. Abstrak. Penelitian ini memiliki tiga tujuan dalam hal experiential marketing, brand loyalty, dan customer satisfaction yang berfokus pada produk Scarlett yang dijual pada applikasi Shopee. Tiga tujuan tersebut diantaranya; (1) Mengetahui gambaran umum perihal variabel yang digunakan; (2) Menginvestigasi pengaruh positif dan signifikan experiential marketing terhadap brand loyalty pada produk Scarlett; dan (3) Menginvestigasi pengaruh moderasi costumer satiscation dalam hubungan antara experiential marketing dan brand loyalty pada brand Scarlett. Metode yang digunakan dalam penelitian ini yaitu dengan melakukan analisis verifikatif pada hasil kuesioner yang disebarkan kepada 158 responden yang kemudian dilakukan penyesuaian kembali, sehingga responden yang digunakan yaitu sebanyak 120 responden. Hasil penelitian ini menunjukkan bahwa experiential marketing memiliki pengaruh positif dan signifikan terhadap brand loyalty, dan customer satisfaction mampu memoderasi nilai experiential marketing terhadap brand loyalty. Sehingga, brand loyalty akan meningkat seiring dengan meningkatnya experiential marketing, selain itu peningkatan brand loyalty oleh experiential marketing tersebut dapat dimoderasi juga peningkatannya dengan customer satisfaction.